Políticas efectivas para reducir la mortalidad infantil en el Perú: ¿Cómo reducir la mortalidad infantil en las zonas más pobres del país? - Beltrán, Arlette (2008)
The purpose of this paper is to find the most effective determinants in reducing child and neonatal mortality, so that policymakers may use policy variables to achieve Millennium Development Goal (MDG) 4: the reduction of child mortality rates by two-thirds by the year 2015 from a baseline of 1992. The paper uses two surveys: the IV Demographic and Family Health Survey (DFHS, 2000), as well as the II Census of Sanitary Infrastructure and Resources of the Health Sector for the year 1999. The duration models (Cox Proportional Hazard model) provided the main methodology in finding the determinants ofneonatal and child mortality, since this is directed towards the survival trajectory of a child in the infant period; in other words, the longer a child manages to stay alive, the better his chances of survival. The evidence suggests that the determinants affecting the neonatal stage most are the healthcare practices for both mother and child: the exclusive use of breastfeeding during the first month after birth, giving birth at a health center, and the provision of health insurance for both. With regard to infant mortality, the results underline the importance of giving birth at a health center, following the vaccination schedule for children of this age, following the number of growth controls, as well as the months of exclusive breastfeeding infants receive.